Model of effective and efficient village fund management policy in Indonesia - Taufik Madjid; Sadu Waisitiono; Tjahya Supriatna; Hadi Prabowo (International Journal Labs, 2024)
The Village Fund is a strategic policy to promote equitable rural development and empower local communities in Indonesia. However, despite notable effectiveness—reflected in high fund absorption, improved village status, reduced unemployment, and increased income—its implementation faces significant efficiency challenges due to overlapping regulations, fragmented authority, and poor institutional coordination. This study aims to analyze the factors affecting the effectiveness and efficiency of Village Fund management and to formulate a comprehensive policy model. Using a qualitative descriptive approach, data were collected through literature review, interviews, focus group discussions, and field observations, followed by coding analysis. The findings reveal that macro-level issues such as regulatory dualism and institutional conflicts cascade into micro-level inefficiencies, including the neglect of community empowerment and underutilized village institutions. To address these challenges, the study proposes a conceptual model that integrates the four formal objects of government science—authority, institutional relations, public services, and welfare—with the